Effects of renal denervation on kidney function and long-term outcomes: 3-year follow-up from the Global SYMPLICITY Registry. (25th March 2019) - Mahfoud, Felix; Böhm, Michael; Schmieder, Roland; Narkiewicz, Krzysztof; Ewen, Sebastian; Ruilope, Luis; Schlaich, Markus; Williams, Bryan; Fahy, Martin; Mancia, Giuseppe
Abstract: Aims: Several studies and registries have demonstrated sustained reductions in blood pressure (BP) after renal denervation (RDN). The long-term safety and efficacy after RDN in real-world patients with uncontrolled hypertension, however, remains unknown. The objective of this study was to assess the long-term safety and efficacy of RDN, including its effects on renal function. Methods and results: The Global SYMPLICITY Registry is a prospective, open-label registry conducted at 196 active sites worldwide in hypertensive patients receiving RDN treatment. Among 2237 patients enrolled and treated with the SYMPLICITY Flex catheter, 1742 were eligible for follow-up at 3 years. Baseline office and 24-h ambulatory systolic BP (SBP) were 166 ± 25 and 154 ± 18 mmHg, respectively. SBP reduction after RDN was sustained over 3 years, including decreases in both office (−16.5 ± 28.6 mmHg, P  <   0.001) and 24-h ambulatory SBP (−8.0 ± 20.0 mmHg; P  <   0.001). Twenty-one percent of patients had a baseline estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 . Between baseline and 3 years, renal function declined by 7.1 mL/min/1.73 m 2 in patients without chronic kidney disease (CKD; eGFR ≥60 mL/min/1.73 m 2 ; baseline eGFR 87 ± 17 mL/min/1.73 m 2 ) and by 3.7 mL/min/1.73 m 2 in patients with CKD (eGFR <60 mL/min/1.73 m 2 ; baseline eGFR 47 ± 11 mL/min/1.73 m 2 ). No long-term safety concerns were observed following the RDN procedure. Conclusion: Long-term data from the Global SYMPLICITY Registry representing the largest available cohort of hypertensive patients receiving RDN in a real-world clinical setting demonstrate both the safety and efficacy of the procedure with significant and sustained office and ambulatory BP reductions out to 3 years.